Step
*
of Lemma
select-from-upto
∀[n,m:ℤ]. ∀[k:ℕm - n].  ([n, m)[k] ~ n + k)
BY
{ Assert ⌜∀d:ℕ. ∀n,m:ℤ.  (((m - n) ≤ d) 
⇒ (∀k:ℕm - n. ([n, m)[k] ~ n + k)))⌝⋅ }
1
.....assertion..... 
∀d:ℕ. ∀n,m:ℤ.  (((m - n) ≤ d) 
⇒ (∀k:ℕm - n. ([n, m)[k] ~ n + k)))
2
1. ∀d:ℕ. ∀n,m:ℤ.  (((m - n) ≤ d) 
⇒ (∀k:ℕm - n. ([n, m)[k] ~ n + k)))
⊢ ∀[n,m:ℤ]. ∀[k:ℕm - n].  ([n, m)[k] ~ n + k)
Latex:
Latex:
\mforall{}[n,m:\mBbbZ{}].  \mforall{}[k:\mBbbN{}m  -  n].    ([n,  m)[k]  \msim{}  n  +  k)
By
Latex:
Assert  \mkleeneopen{}\mforall{}d:\mBbbN{}.  \mforall{}n,m:\mBbbZ{}.    (((m  -  n)  \mleq{}  d)  {}\mRightarrow{}  (\mforall{}k:\mBbbN{}m  -  n.  ([n,  m)[k]  \msim{}  n  +  k)))\mkleeneclose{}\mcdot{}
Home
Index